Gender Influence of College Tutors Perception of ICT Integration in Teaching and Learning in Volta Region of Ghana - Lokpo, Cephas Lokpo; Kumah, Maxwell Seyram (Journal of Education and Practice, 2023)
Purpose: One of the key areas of research in education has been the gender variations in academic performance. This seems to be reflecting among teachers well, particularly because it may reveal potential gaps and inequalities in particular areas. While these disparities have mostly been studied in traditional fields like math, reading, and science, the body of experimental research on ICT literacy is far smaller yet is rife with interesting results. This study investigated the sex influence on Colleges of Education (CoEs) tutors' perception of ICT integration in teaching in Volta region of Ghana. Methodology: The study employed a cross-sectional analytic survey design with 121 participants. The Tutor ICT Integration Perception (TIIP) questionnaire which consists of 12 items was used to elicit information from selected tutors. Data collected was analysed using a median and Mann- Whitney U sample t - test. Three variables of tutor ICT integration perception were considered; tutor competence, improve tutors' teaching and student learning and no effect on lesson delivery in relation to sex influence. Findings: The result showed that majority of the tutors disagreed with most of the statements and there was no significant sex difference influence on tutor perception. It is concluded that integration or no integration of ICT in the classrooms should be anticipated from all tutors irrespective of their gender. Unique Contribution to Theory, Policy and Practice: The unique contribution of tutors' perception of ICT integration in teaching and learning is that it provides valuable insights into how technology is being used in the classroom and the effectiveness of its integration. By understanding tutors' perceptions of ICT integration, educators and policymakers can make informed decisions about how to use technology effectively in the classroom, ultimately improving the quality of education for students.